PENGARUH PENDIDIKAN, PELATIHAN DAN KEMAMPUAN KERJA TERHADAP PENGEMBANGAN SUMBER DAYA MANUSIA PADA KANTOR KECAMATAN LENTENG KABUPATEN SUMENEP - jurnalmap map; Abdul Gafur; Nugroho Mardi Wibowo; Muninghar ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT The purpose of this study was to study the analysis of education, training and work skills related to the improvement of human resources in the Lenteng District Office of Sumenep Regency; to find out and analyze whether education, training and work ability have a significant and partial influence on the development of Human Resources at the Lenteng District Office in Sumenep Regency. This type of research is explanatory research using quantitative research. This research was conducted at the Lenteng District Office in Sumenep Regency with a total sample of 34 people. The sampling technique uses the total sampling method. The results of the study showed that simultaneously, education, training and work ability were significant for the development of human resources at the Lenteng District Office in Sumenep Regency. Partially, education, training and significant work ability to develop human resources at the Lenteng District Office in Sumenep Regency. Based on the results of the t test published in the Lenteng District Office of Sumenep Regency. Keywords: education, training, work ability, HR development